2015
DOI: 10.1155/2015/632760
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll‐Like Receptors 2 and 4 and Related Cytokines in Patients with Hepatic Cystic and Alveolar Echinococcosis

Abstract: Several studies have demonstrated the important role of Toll-like receptors in various parasitic infections. This study aims to explore expression of Toll-like receptors (TLRs) and related cytokines in patients with human cystic echinococcosis (CE) and alveolar echinococcosis (AE). 78 subjects including AE group (N = 28), CE group (N = 22), and healthy controls (HC, N = 28) were enrolled in this study. The mRNA expression levels of TLR2 and TLR4 in blood and hepatic tissue and plasma levels related cytokines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…KEGG pathway analysis further demonstrated that the mRNAs targeted by the miRNAs were mainly involved in the regulation of signal transduction, infectious diseases, and the immune system, which have been widely researched and demonstrated to be associated with the functions of exosomes (Coakley et al, 2015 ). The predicted host target genes are involved in the inflammatory responses, including encoding members of the TNF, TLR, MAPK, and NF-κB signaling pathways, which have previously been documented to modulate cytokines during chronic E. granulosus infection (Refik et al, 2005 ; Tuxun et al, 2015 ; Labsi et al, 2018 ; Zhang et al, 2019 ). Additionally, the most abundant miRNAs were predicted to participate in Th1 and Th2 cell differentiation, Th17 cell differentiation, and IL-17 signaling pathway, and these immune responses occur during E. granulosus infections (Tuxun et al, 2012 ; Labsi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…KEGG pathway analysis further demonstrated that the mRNAs targeted by the miRNAs were mainly involved in the regulation of signal transduction, infectious diseases, and the immune system, which have been widely researched and demonstrated to be associated with the functions of exosomes (Coakley et al, 2015 ). The predicted host target genes are involved in the inflammatory responses, including encoding members of the TNF, TLR, MAPK, and NF-κB signaling pathways, which have previously been documented to modulate cytokines during chronic E. granulosus infection (Refik et al, 2005 ; Tuxun et al, 2015 ; Labsi et al, 2018 ; Zhang et al, 2019 ). Additionally, the most abundant miRNAs were predicted to participate in Th1 and Th2 cell differentiation, Th17 cell differentiation, and IL-17 signaling pathway, and these immune responses occur during E. granulosus infections (Tuxun et al, 2012 ; Labsi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma was prepared and stored at −80 °C until use 37 . PBMCs were isolated using the Ficoll-Hypaque (Sigma-Aldrich, St Louis, MO, USA) density gradient centrifugation technique 37 .…”
Section: Samples Preparationmentioning
confidence: 99%
“…Tuxun, et al [21] IL-23 levels were significantly higher in the AE group than in the healthy control group. Tuxun et al [22] Viable proliferating E. multilocularis metacestode vesicles induced significant IL-8 and MCP-1 production by peripheral blood cells from AE patients.…”
Section: Resultsmentioning
confidence: 99%